Audience Reception Analysis of Feminism in Difficulty Being Woman Mata Najwa 2 - Sekar Kedaton, Kirana Ratu; Dewi Swastika, Gabriela Laras (Institut Agama Islam Negeri Kendari, 2024)
Social media exposure is impossible to avoid in this era and changes in communication behavior for individuals and groups to become more open and active. Based on Report data for 2023, there were 139 million YouTube users in Indonesia as of January 2023, which is estimated to increase to 81.82% of the population in 2026. This bombastic number is considered effective for spreading campaigns for women's rights and feelings through social media, which discusses stereotypes, gender equality, and feminism contained in Wati's 2022 research on Spreading Gender Equality Values Through YouTube. YouTube content that can accommodate it is